Education for peace and vocational training: an approach based on documentary research - Torres Gómez, Myriam Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In the continent’s current socio-political situation, there is a trend towards war, xenophobia, hate, exclusion, terror, and an understanding of others as “enemies”. This panorama reveals expressions of violence caused by the imposition of power that ignores diversity-based rights. This article shows the findings and the pedagogical challenges derived from a qualitative research project using the documentary method and including an analysis of more than forty documents. It also provides ways of rethinking the place education in and for peace in vocational training. One of the findings is the emerging didactic approach based on educational practices regarding peace in the context of social sciences at universities. Such approach focuses on addressing peace from the perspective of macro-social and socio-political conflicts instead of educating in and for peace in the context of everyday life